(untitled) (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: This study aims to describe the knowledge and practice of using antibiotics among women with children under 2 years old living in 3 wards in Thai Binh city in 2023. Method: An epidemiological study with a cross-sectional survey was conducted on 380 mothers of children under 2 years old living in 3 wards in Thai Binh in 2023. The descriptive analysis was used to describe the knowledge and practice of using antibiotics among study participants. Results: This study was conducted on 380 study participants. Of these, 86.3% had heard of antibiotics, and 61.6% used antibiotics to treat their children’s diarrhea. The proportion of participants who met the knowledge standard and were aware of important medical guidelines when using antibiotics was 40.5% and 80.5%, respectively. Additionally, 35.9% of study participants demonstrated good practices in using antibiotics. Conclusion: This study contributes to the ongoing conversation about antibiotic stewardship and the need for better public health initiatives to promote proper medication use, ultimately improving health outcomes and combating the threat of antibiotic resistance.